2019
DOI: 10.1128/aem.00829-19
|View full text |Cite
|
Sign up to set email alerts
|

Biopearling of Interconnected Outer Membrane Vesicle Chains by a Marine Flavobacterium

Abstract: Large surface-to-volume ratios provide optimal nutrient uptake conditions for small microorganisms in oligotrophic habitats. The surface area can be increased with appendages. Here, we describe chains of interconnecting vesicles protruding from cells of strain Hel3_A1_48, affiliating with Formosa spp. within the Flavobacteriia and originating from coastal free-living bacterioplankton. The chains were up to 10 μm long and had vesicles emanating from the outer membrane with a single membrane and a size of 80 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 60 publications
4
41
0
Order By: Relevance
“…These chains of interconnected vesicles enlarge the cell surface of bacteria resulting into increased surface enzymes per cell volume ( Bar-Ziv and Moses, 1994 ). These vesicle chains are well reported in various species of Flavobacteria such as F. columnare , F. psychrophilum and also in strain Hel3_A1_48 of a marine flavobacterium ( Fischer et al, 2019 ). Apart from these, Francisella novicida , Myxococcus xanthus , and Shewanella oneidensis also showed chains of vesicles on their cell surfaces ( Subramanian et al, 2018 ; Fischer et al, 2019 ).…”
Section: Surface Appendages In Bacteriasupporting
confidence: 62%
“…These chains of interconnected vesicles enlarge the cell surface of bacteria resulting into increased surface enzymes per cell volume ( Bar-Ziv and Moses, 1994 ). These vesicle chains are well reported in various species of Flavobacteria such as F. columnare , F. psychrophilum and also in strain Hel3_A1_48 of a marine flavobacterium ( Fischer et al, 2019 ). Apart from these, Francisella novicida , Myxococcus xanthus , and Shewanella oneidensis also showed chains of vesicles on their cell surfaces ( Subramanian et al, 2018 ; Fischer et al, 2019 ).…”
Section: Surface Appendages In Bacteriasupporting
confidence: 62%
“…One recently discovered member of Flavobacteriaceae , Formosa strain Hel3_A148, revealed another strategy for the optimization of nutrient uptake that involves BMV release (Fischer et al . 2019 ). As a result of a process called ‘biopearling’—the membranes of these bacteria protrude and form up to 2-μm-long tubular appendages and start to oscillate due to abiogenic physical forces resulting from the competition between membrane curvature and tension that together introduce instability in the tubular structure and produce a chain of linked with short neck vesicles or ‘pearls’; see Box 2 and Fig.…”
Section: The Role Of Bmvs In Bacterial Ecologymentioning
confidence: 99%
“…4B (Fischer et al . 2019 ). Proteomics studies of the BMVs of this strain have shown that the BMVs are enriched in porins (the OmpC-like type), hydrolytic enzymes (including endonucleases, peptidases and glycoside hydrolases), TonB-dependent proteins and gliding motility-associated proteins, while BMVs have also been found to exhibit laminarin-binding properties, which suggests a role in carbohydrate binding and utilization (Fischer et al .…”
Section: The Role Of Bmvs In Bacterial Ecologymentioning
confidence: 99%
“…OMV formation is ubiquitous and has many documented functions 9 . OMEs are less commonly observed, remain attached to the cell, and various morphologies can be seen extending from single cells including Myxococcus xanthus 14,15 , flavobacterium strain Hel3_A1_48 8 , Vibrio vulnificus 10 , Francisella novicida 28 , Shewanella oneidensis 7,2931 , and as cell-cell connections in Bacillus subtilis 3234 and Eschericia coli 35 . Several bacterial proteins have demonstrated membrane tubule formation capabilities in vitro 16,3640 , but despite the growing number of reports, proteins involved in shaping bacterial membranes into OMV/Es have yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Several bacterial proteins have demonstrated membrane tubule formation capabilities in vitro 16,3640 , but despite the growing number of reports, proteins involved in shaping bacterial membranes into OMV/Es have yet to be identified. Recently, researchers have begun to suspect that OMV and OME formation has some pathway overlap 8 , and it is proposed that proteins are necessary to stabilize these structures 13 .…”
Section: Introductionmentioning
confidence: 99%